Analisis Sistem Penyusunan Anggaran Biaya Operasional Pada PT. Sarana Agro Nusantara Guna Menilai Kinerja Keuangan - Adellia, Adellia; Septriawan, Muhammad Reza; Iskandar, Eddy (Worksheet : Jurnal Akuntansi, 2023)
This research aims to determine the operational cost budget of PT. Sarana Agro Nusantara for the 2018-2021 period. The operational budget is a plan for all company activities to achieve its goals within a certain time period. Every company is always expected to experience times full of uncertainty, which will give rise to problems in choosing from various alternative policies that it will pursue in implementing its business activities. The type of research used in this research is descriptive qualitative research. The data sources used in this research are primary and secondary. The results of this research are that there is a difference between the budget and realization in the 2018-2021 period and there are budget deviations caused by internal and external factors.Keywords : Budget, Operational Costs, Financial Performance